Parent motivational climate, sport enrollment motives, and young athlete commitment and enjoyment in year-round swimming - Williams, R. E.; Habeeb, C. M.; Raedeke, T. D.; Dlugonski, D.; DuBose, K. D. (International Journal of Exercise Science, 2022)
Parents are known to influence the athlete sport experience through motivational climates. Athletes` perception of motivational climates and their own motives for sport participation influence enjoyment and long-term sport commitment. It is unknown, however, the extent parent motives for initially enrolling their child in a year-round sports program associate with children`s sport participation enjoyment and commitment. The purposes of this study were to (a) determine parent motives for enrolling their child (5-8 years) in year-round swimming and (b) explore the relationships of parent motives and motivational climates with child enjoyment and commitment. Parents (n = 40) completed questionnaires on enrollment motives and motivational climate, while children (n = 40) answered questions on enjoyment and commitment. Of the seven motives measured, parents enrolled children in swimming primarily for fitness benefits (M = 4.5, SD = .45) followed by skill mastery (M = 4.31, SD = .48) and fun (M = 4.10, SD = .51) reasons. Findings revealed the fitness motive was moderately, negatively correlated with the success-without-effort facet of a performance climate (r = -.50, p < .01). The fun motive was moderately, positively associated with commitment (r = .43, p < .01). Parent motives for enrolling their child in sport may impact the young child sport experience and long-term sport continuation via motivational climates, enjoyment, and commitment.